OPTIMIZING DEMOGRAPHIC DIVIDEND IN PERSPECTIVE OF RETURN ON EDUCATION IN EAST JAVA: TO SCHOOL, TO WORK, OR TO ENTREPRENEUR? - R. Dimas Bagas Herlambang (East Java Economic Journal, 2018)
Human capital highly affects economics productivity. Thus, education plays an important factor in every demographic dividend. This study will estimate the return on education to paid-employment and self-employment in East Java using SAKERNAS 2012. Using Mincerian specification and Sohn model, this study analyzed the baseline model and to analyse further in self-employment. This study will also compare result in East Java with National and other Java province. Results from estimation found that return on education in East Java is generally higher than national, but lower than West Java. As for self-employment, return on education in East Java is lower than paid-employment, but in the lowest magnitude if compared with National and other Java region. Labor market flexibility that analyzed in this study also shows that East Java relatively more flexible. As a matter of opportunity cost, the low return rate of education in East Java demand some adjustment in education and labor market policy to optimize the economic outcome.